PENGEMBANGAN MODEL PEMBELAJARAN SERVIS ATAS DAN BAWAH BOLA VOLI SISWA SEKOLAH MENENGAH PERTAMA - Indri Lorian (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2023)
, and low student skills in serving well. The service learning model can increase students' interest in learning. Thus the needs analysis carried out by students requires a learning model that arouses students' interest in learning PJOK students because many students are not yet able to serve volleyball properly and correctly. The aim is to develop a learning model for serving volleyball. This type of research is Research and Development (R&D). Model development uses the ADDIE model. Then the validation test was carried out by 3 validators (team of experts), the practicality test was carried out by the PJOK teacher, after the model was categorized as valid and practical, then an effectiveness test was carried out by 20 students by carrying out the under serve and over serve tests. The results of the research on developing a model of the material taught underhand serve and overhand volleyball in the validity test obtained percentage data with an average of 85.24% categorized as very valid, practicality test by PJOK teachers with a percentage of 96.67% and students with a percentage of 85.4 % is categorized as very practical, while the effectiveness test with a percentage of 75% is categorized as very effective. Based on the results obtained, the volleyball service development model is categorized as valid, practical and effective. It can be concluded that learning with this volleyball service model can be applied.